METABOLIC SURGERY FOR COMPLEX PHENOTYPES OF METABOLIC SYNDROME: from obesity index to hormonal and gastrointestinal profiles - Khamdamov , I.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Metabolic syndrome (MetS) is a heterogeneous condition influenced by diverse endocrine, anatomical, and inflammatory profiles. As bariatric surgery evolves into metabolic surgery, understanding patient-specific phenotypes becomes essential for personalized treatment. Objective: To review and analyze current evidence on how metabolic surgery outcomes are affected by individual variations in insulin resistance, GERD, NAFLD, gut hormone response, and anatomical gastric parameters. Methods: A narrative literature review was conducted using PubMed, Scopus, and Embase, including clinical trials and cohort studies from 2005 to 2024. Key search terms included «metabolic syndrome», «bariatric surgery», «phenotypes», «GERD», «NAFLD», and «gut hormones». Results: Evidence shows that patients with high HOMA-IR and low C-peptide respond better to malabsorptive procedures like OAGB or RYGB, while those with mild insulin resistance and active GLP-1 signaling benefit from restrictive options such as LSG. The presence of GERD and anatomical variation in stomach axis influences surgical choice, with anti-reflux modifications proving superior in high-risk patients. NAFLD, increasingly viewed as a «hepatocentric» component of MetS, may also require tailored surgical strategies. Gut hormone dynamics and microbiota profiles are emerging as key modifiers of metabolic outcomes. Conclusion: Metabolic surgery should no longer be viewed as a singular approach. Recognizing and stratifying phenotypic complexity in MetS patients allows for more rational procedure selection and improved long-term outcomes. A shift toward algorithm-driven, phenotype-adapted surgery is both necessary and imminent. Keywords: Metabolic syndrome, bariatric surgery, phenotyping, insulin resistance, GERD, NAFLD, GLP-1.